Freezing Damage Control of Railway Subgrade Miniature Shields in Cold Climatic Regions: Construction Technology Optimization via Numerical Simulation - Caolin Qing; Shaolong Jie; Zurun Yue; Liwei Wang; Bingcheng Wang (Advances in Civil Engineering)
Microshield structure replacement technology is commonly used to control the freezing damage of railway roadbeds, featuring high efficiency and easy operation. However, improper disposal of measures in the construction process will still cause excessive deformation of the line and endanger the safety of train operations. On the background of a subgrade freezing damage improvement and speed improvement project of the Xige section of Quinghai–Tibet railway, this study performed numerical simulation of the microshield based on the measured data of the field automatic monitoring system to improve the operation safety of the existing lines and optimize the construction technology of the microshield. The effect of the changes in the microshield segment material, construction process, and formation loss on the settlement of the operating railway subgrade was analyzed to control the construction disturbance settlement of the existing operating line. The results obtained show that the overall settlement deformation of the line is small when the steel pipe is used as the shield segment, which meets the safety management requirements of the existing operating line. When PE tube segments are used for construction, construction measures should be strictly controlled to reduce the effect of settlement deformation on the operational lines. When steel pipe segments are used, the settlement generated by the construction process from both sides to the middle is minimal. When PE tube segments are adopted in the construction, the settlement generated by the construction process with unilateral advancement and an interval of two pipe diameters is the least, producing unimodal settlement curve of the line. The latter features a double peak when the shield pipe interval is three pipe diameters or more. When using PE tube pieces for the microshield construction, it is necessary to strictly control the formation loss rate within 10% by optimizing the construction control measures.